Generalized Fractional Integration of the H-Function Involving General Class of Polynomials - Dinesh KUMAR; Praveen AGARWAL; Sunil Dutt PUROHIT (Walailak Journal of Science and Technology, 2014)
In the present paper, we consider 2 integral transforms involving the Appell function F3 in the kernels. They generalize the fractional integral operators given by Saigo (1978). Formulas for compositions of such generalized fractional integrals with the product of the -function and a general class of polynomials are proved. The results are established in terms of -function due to Inayat-Hussain (1987(a), 1987(b)). The obtained results of this paper provide an extension of the results given by the literature.